The blue light-dependent LOV-protein LdaP of Dinoroseobacter shibae acts as antirepressor of the PpsR repressor, regulating photosynthetic gene cluster expression - Pucelik, Saskia; Becker, Miriam; Heyber, Steffi; Wöhlbrand, Lars; Rabus, Ralf; Jahn, Dieter; Härtig, Elisabeth (Frontiers in Microbiology, 2024)
In the marine -proteobacterium Dinoroseobacter shibae more than 40 genes of the aerobic anoxygenic photosynthesis are regulated in a light-dependent manner. A genome-wide screen of 5,605 clones from a D. shibae transposon library for loss of pigmentation and changes in bacteriochlorophyll absorbance identified 179 mutant clones. The gene encoding the LOV-domain containing protein Dshi_1135 was identified by its colorless phenotype. The mutant phenotype was complemented by the expression of a Dshi_1135-strep fusion protein in trans. The recombinantly produced and chromatographically purified Dshi_1135 protein was able to undergo a blue light-induced photocycle mediated by bound FMN. Transcriptome analyses revealed an essential role for Dshi_1135 in the lightdependent expression of the photosynthetic gene cluster. Interactomic studies identified the repressor protein PpsR as an interaction partner of Dshi_1135. The physical contact between PpsR and the Dshi_1135 protein was verified in vivo using the bacterial adenylate cyclase-based two-hybrid system.In addition, the antirepressor function of the Dshi_1135 protein was demonstrated in vivo testing of a bchF-lacZ reporter gene fusion in a heterologous Escherichia coli-based host system. We therefore propose to rename the Dshi_1135 protein to LdaP (light-dependent antirepressor of PpsR). Using the bacterial two-hybrid system, it was also shown that cobalamin (B12) is essential for the interaction of the antirepressor PpaA with PpsR. A regulatory model for the photosynthetic gene cluster in D. shibae was derived, including the repressor PpsR, the light-dependent antirepressor LdaP and the B12dependent antirepressor PpaA.